Impact of carbon dioxide and nitrogen addition on the global structure of hydrogen flames. (1st March 2023) - Eckart, S.; Pio, G.; Zirwes, T.; Zhang, F.; Salzano, E.; Krause, H.; Bockhorn, H.
Highlights: Experimental investigation on premixed H2 -CO2 -air flames at different compositions. Identification of thermodiffusive unstable regimes for premixed H2 -CO2 combustion. One- and two-dimensional numerical simulations of the flame structure. Quantification of chemical and thermal effects of CO2 on flame dynamics. Direct comparison of the performances of different kinetic mechanisms. Abstract: Investigations into the combustion characteristics and flame structure of hydrogen/carbon dioxide/air flames have been carried out experimentally and numerically. The aim was to determine the variations of the combustion properties and flame shape for different carbon dioxide dilutions in the H2 -air mixtures. For this purpose, premixed flames at various compositions of hydrogen-carbon dioxide mixtures are investigated experimentally in a heat flux burner configuration at varying equivalence ratios from 0.5 to 1.1, fresh gas temperatures and under atmospheric conditions. Optical investigations are performed to detect the number of cellular structures on the flame front. Furthermore, the laminar burning velocity and the influence of carbon dioxide addition were examined numerically. A detailed kinetic mechanism was implemented for the identification of the most representative intermediates via a reaction path analysis, and the most influential species and reactions are identified through sensitivity analyses at conditions relevant to the studied application. Considering the nature of the adopted mechanism, the presence of CO2 has the potential to shift the production/consumption rate of some hydrogen-containing radicals. Hence, numerical investigations employing an inert species having the same thermodynamic and transport properties as CO2 (referred to as fictitious CO2, FCO2 ) were compared and discussed in this work. To investigate the effect of CO2 on the dynamics of the hydrogen flames, one-dimensional and two-dimensional detailed simulations of the flame structure have been carried out. The addition of CO2 makes the flame more prone to thermo-diffusive instabilities through a decrease in the mixture's thermal diffusivity. This results in a decrease of the Markstein number and an enhanced formation of characteristic cellular structures on spherically expanding flames. Overall, the comparison between the experimental and numerical investigations reveals similar conclusions.